Pengembangan Aplikasi Arsip Berbasis Web di UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan - El Ikhwan, Muhammad Taufiq; Faisal, Ahmad (Jurnal Dinamika Informatika, 2023)
The development of information technology has changed the paradigm of archive management, giving rise to the need for digitization and web-based applications. UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, a higher education institution, faces obstacles in manual archive management, such as limited accessibility, risk of losing physical archives, and inefficiency in searching. In light of this, this research aims to develop a web-based application that focuses on records management, with the aim of improving the quality of service to all members of the academic community. This research involves understanding the principles of effective records management, namely records management that is minimal, meaningful, economical, and easy to find. The research also explores the efforts to develop a webbased archive application at UIN Syahada Padangsidimpuan as well as the inhibiting and supporting factors in the process. The results of this study are expected to provide guidance for other higher education institutions in adopting information technology to improve efficiency and services to stakeholders.